THE APPLICATION OF SIMPEG (PERSONNEL MANAGEMENT INFORMATION SYSTEM) CORRELATED WITH CUSTOMER SATISFACTION - Hasanah, Fitri; Septiani, Dewi; D, Asti Nurul; M, Dzikri Ahfadz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In the management of educational institutions, information is crucial.Information isn't simply necessary for external interests, but it's additionallyhighly influential for the institution itself. SIMPEG is an application designedby and utilized by MTsNacross the whole of Bandung to manage the personnelinformation system. Personnel management services at MTsN across thewhole of Bandung can be managed using SIMPEG, allowing institutionalleaders to observe the strengths and limitations of the servicesoffered. Thefocus of this research is to learn how SIMPEG is applied, how customersatisfaction are with civil servant administrative services, and to verify theresearch hypothesis. This research belongs to the field of quantitative researchand employsthe descriptive correlation technique. The researcher was using arandom sampling method when collecting the sample. Researchers used aLikertscalemodelquestionnaireasmaindataanddisseminatedquestionnaires to 60 samples. According to the findings of this research, thereis a relationship between SIMPEG implementation and customer satisfactionwith civil servant administration services at MTsN all through the city ofBandung, with a value of 0.442 indicating the intensity of the relationship.Thus, Ha is approved, and there is a favorable and substantial connectionbetween SIMPEG implementation and customer satisfaction with civil servantadministration services at MTsN all through the city of Bandung.